2005
DOI: 10.1161/01.atv.0000151624.45775.13
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor–Factor VIIa Signaling

Abstract: Abstract-How does tissue factor (TF), whose principle role is to support clotting factor VIIa (FVIIa) in triggering the coagulation cascade, affect various pathophysiological processes? One of the answers is that TF interaction with FVIIa not only initiates clotting but also induces cell signaling via activation of G-protein-coupled protease activated receptors (PARs). Recent studies using various cell model systems and limited in vivo systems are beginning to define how TF-VIIa-induced signaling regulates cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
139
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 127 publications
2
139
0
3
Order By: Relevance
“…A number of gain-and loss-of-function studies have shown that genetic modulation of TF promotes tumor cell invasion/migration and metastasis in vivo (20 -22). Current studies indicate that the ternary TF⅐FVIIa⅐Xa complex, efficiently signals through PAR-1 or PAR-2 in a FXa-dependent manner (23,24) and cross-talks with several important cellular signaling pathways, including MAPK pathway, Src family tyrosine kinases, and NFB members (25,26). Considering these many provocative findings, we have presently investigated the possible role of TF⅐FVIIa and the induced signaling pathways in regulation of MDA-9/syntenin expression.…”
mentioning
confidence: 99%
“…A number of gain-and loss-of-function studies have shown that genetic modulation of TF promotes tumor cell invasion/migration and metastasis in vivo (20 -22). Current studies indicate that the ternary TF⅐FVIIa⅐Xa complex, efficiently signals through PAR-1 or PAR-2 in a FXa-dependent manner (23,24) and cross-talks with several important cellular signaling pathways, including MAPK pathway, Src family tyrosine kinases, and NFB members (25,26). Considering these many provocative findings, we have presently investigated the possible role of TF⅐FVIIa and the induced signaling pathways in regulation of MDA-9/syntenin expression.…”
mentioning
confidence: 99%
“…Cette activation de la voie du facteur tissulaire -dite intrinsèque -conduit également à la consommation des plaquettes. De plus, le complexe FT-FVIIa est un élément de signalisation connu notamment pour induire dans les cellules un afflux de Ca 2+ ; c'est aussi un facteur pro-inflammatoire (via l'induction d'IL-6 et d'IL-8) [34]. Différentes protéines recombinantes (rNAPC2 et APC/Xigris) inhibitrices de la voie du facteur tissulaire ont montré leur efficacité dans le traitement de l'infection à virus Ebola chez le singe [35,36].…”
Section: Le Facteur Tissulaireunclassified
“…Binding of FVIIa to TF on cell surfaces not only triggers the coagulation cascade, but also induces intracellular signaling; however, the latter process depends on the availability of specific protease-activated receptors (PAR) on the cell surface, and on other cell-associated proteins near TF-FVIIa complexes on the cell membrane (13). Thus, not all cells that express TF are capable of transmitting cell signaling in response to FVIIa binding.…”
Section: Fviia Association With Tf-expressing Cellsmentioning
confidence: 99%